PELATIHAN PENULISAN BUKU AJAR INOVATIF BER-ISBN: UPAYA PENINGKATAN PROFESIONALISME DOSEN - Khasanah, Uswatun; Trisnawati, Septian Nur Ika (Tahta Media Grup, 2023)
Textbooks are an important learning resource for lecturers and students in universities. Lecturers have a central role in transferring knowledge through textbooks. One way to improve lecturers' competence in preparing modules and textbooks is through training and mentoring. This community service activity targets PTN / PTS lecturers throughout Indonesia, with the number of participants reaching 238 lecturers. This activity involves several stages, namely planning, implementation (including presentation of material by speakers, discussions, and work practices), and evaluation. The results of this activity showed that the lecturers/participants were able to participate in the activity interactively, some of them succeeded in making textbooks, and the participants were very satisfied with the activities carried out. This activity also succeeded in publishing 16 books with ISBNs through publishers who are members of IKAPI. It is recommended that this activity be carried out more intensively by involving more PTN / PTS lecturers, as well as with a more comprehensive form of training and mentoring, covering topics such as monographs, reference books, and book chapters, until all books prepared are published with ISBNs.